Implementasi Metode 4A Melalui Pengembangan Destinasi Wisata Pantai Bangsring Banyuwangi - Joko Triyono (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The purpose of this study was to analyze the existence of the Bangsring Nature Beach Tourism object, Wongsorejo District, Banyuwangi with the 4A concept (Attractions, Accessibility, Amenities, and Activities). The research was carried out from January to March 2023. The approach used was narrative qualitative research, the research results were presented descriptively. The existence of data obtained from interviews, observation, documentation, and literature review. The results of the analysis based on the 4A analysis concept show that the implementation of the 4A method is said to be quite effective in attracting tourism, so they want to visit tourist attractions. Tourist attractions are varied by utilizing their natural potential, access to locations is easily accessible and accessible, tourism support facilities are available, and tourism management involves various stakeholders initiated by tourism awareness groups (Pokdarwis). Thus, the management of natural tourism has a positive impact both socio-culturally, preserving the natural environment, and improving the economy of the surrounding community.